2018
DOI: 10.1177/1533317518755332
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Help-Seeking Motivation in the Assessment of Cognitive Decline

Abstract: Diagnostic assessments for dementia include the evaluation of subjective memory impairment, dementia worries, or depressive symptoms. Data on the predictive value of these factors remain unclear, and varying help-seeking behavior may contribute to this finding. We investigate whether differentiating help-seeking motivation from other psychological factors associated with cognitive impairment would enhance the prediction of diagnostic outcomes in a memory clinic. We obtained information on help-seeking motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Third, MMSE scores were not adjusted for educational level. Finally, there is a lack of information collected on different factors known to be related to help-seeking intentions, such as personal exposure to AD, the perception of social support, disease knowledge, motivational aspects, and cultural and race factors ( 13 , 33–35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, MMSE scores were not adjusted for educational level. Finally, there is a lack of information collected on different factors known to be related to help-seeking intentions, such as personal exposure to AD, the perception of social support, disease knowledge, motivational aspects, and cultural and race factors ( 13 , 33–35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our prior data on the diagnostic value of clinical parameter compositions [16], we utilized a discriminance analysis [17] to investigate whether individual performance across different neurocognitive domains would differentiate between the diagnostic groups "depressive MCI (dMCI)", "amnestic MCI (aMCI)," and "other" (MCI; neither depressive nor amnestic). We further performed a multivariate analysis of variance (MANOVA) to control for age-specific effects on group discrimination for each parameter included in the discriminance analysis.…”
Section: Statistical Analysesmentioning
confidence: 98%
“…Health access barriers to HS (e.g., transportation, lack of specialized care, limited resources) for memory concerns are particularly heightened in traditionally underserved populations such as minoritized race and ethnic groups, as well as rural populations. 32,62,[69][70][71][72][73][74][75] For instance, a recent literature review exploring cross-cultural differences in dementia found that minoritized ethnic older adults tended to present with worse cognition and at later stages of dementia than non-Hispanic Whites at the time of their first evaluation, 42 suggesting distinctive HS barriers between these 2 groups, among other factors (e.g., illness perception differences, culturally associated beliefs, personal beliefs, language proficiency, level of acculturation, etc.) 42,48,76 .…”
Section: Health Access Barriers Related To Hsmentioning
confidence: 99%